Urban aquaculture. Water-sensitive transformation of cityscapes via blue-green infrastructures. - Bürgow, Grit (Shaker, 2014)
Blue-green infrastructures can contribute to local resource and food security. Their capability to regenerate human and ecosystem livelihoods in a multifunctional manner makes them valuable building blocks of a water-sensitive city and landscape development. In this book, the author develops the concept of an urban aquaculture unifying old cultural techniques from different regions of the world with new know-how. Her holistic approach weaves aspects of history together with the future development of the city and landscape encompassing themes of ecology, technology, learning and design. The unfolding perspective touches everyday life questions: It proposes not only a reconstruction of urban infrastructure, but also a change of urban lifestyle. Traditional and contemporary types of aquaculture are the focus of the observations. Their services are "blue-green" - the regeneration of fresh water, the production of food and the support of biodiversity. Water-farming is the original core of aquaculture; classic forms illustrated are swimming gardens, fishponds and water-farm greenhouses. In addition to water-farming, the author singles out the concept of "water-wellbeing" in cities; bathing ships and river swimming pools are part of this. A third building block is a "water-living culture," which generally describes urban life at and in the water. The concept runs through approaches at the building design level, called "aquatecture," and in the form of "aquapunctures" at a participative-communicative level. Case studies deepen these conceptional considerations. The city-wide level illuminates aspects of daily use of technical infrastructure and the accompanying landscape change. The project level investigates multifunctional design approaches and services and ways of an effective spatial and resource utilization through combined water and food production. Last, but not least, it shows the possibilities of participation and applied learning within the scope of infrastructural design and management processes.
Keywords: Stadtplanung; Wasserplanung; Stadtraum; Stadtlandschaft; Stadtökologie; Fallstudie; Nutzung; Erholung; Fluss; Dach; Gewächshaus; Wasseraufbereitung; Teich; Fischerei; Transformation; Aquakultur; Nahrungsmittelproduktion